Analysis of the Effect of Prices, Promotions and Products on Purchase Interest Impacts on Consumer Satisfaction of VIVO Brand Mobile Phones in South Tangerang Region - Jasmani Jasmani; Sutiman Sutiman; Denok Sunarsi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
Vivo, one of the brand new handphone brands, entered Indonesia in 2014. Not just trying to exist in the smartphone industry, but Vivo also has the ambition to become a new giant force in the world. This study aims to determine the effect of prices, promotions and products on buying interest that has an impact on consumer satisfaction VIVO brand mobile phones in the South Tangerang area. The method used was explanatory research with a sample of 96 respondents. The analysis technique uses instrument testing, classical assumption test, regression testing, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study significantly influence the price of buying interest by 25.4%, the hypothesis test obtained significance 0,000 <0.05. Promotion has a significant effect on buying interest by 40.2%, hypothesis testing is obtained significance of 0,000 <0.05. The product has a significant effect on buying interest of 23.8%, the hypothesis test obtained a significance of 0,000 <0.05. Price, promotion and product simultaneously had a significant effect on buying interest of 49.3%, the hypothesis test obtained a significance of 0,000 <0.05. Purchasing interest has a significant effect on customer satisfaction by 48.5%, the hypothesis test is obtained significance of 0,000 <0.05. Towards consumer satisfaction of 45.5%, the hypothesis test is obtained significance of 0,000 <0.05.